Alternatives to Glyphosate for Palmer Amaranth Control in Wheat Stubble - D. E. Peterson; C. Thompson; C. L. Minihan (Kansas Agricultural Experiment Station Research Reports, 2017)
Glyphosate-resistant Palmer amaranth has become a serious weed problem in fields following wheat harvest. A field experiment was established in 2016 near Manhattan, KS, to evaluate herbicide alternatives to glyphosate for Palmer amaranth control in wheat stubble. The two most effective postharvest herbicides for control of Palmer amaranth were Gramoxone (paraquat) or Sharpen (saflufenacil). Clarity (dicamba) and 2,4-D treatments provided suppression of Palmer amaranth, but were inconsistent, and often some plants survived and produced viable seed. The tank-mix of Clarity plus 2,4-D was more effective than either herbicide alone, but not as good as Gramoxone or Sharpen.
Keywords: Palmer amaranth; large crabgrass; fallow; weeds